'Outward Bound' (reverse) - Unknown (Tufts Archival Research Center, 2014)
6.1 x 8.1 in., photographic print. Back of photograph showing Bob Nicholson and Muriel Simonson performing in 'Outward Bound,' a play produced at Tufts in March, 1929.